Effect of different fishmeal levels in diets on growth performance, tissue morphology, intestinal microflora, and muscle volatile compounds of grass carp - Wang, Guangwei; Luo, Wenle; Zhang, Xuexue; Sun, Gege; Tong, Fangle; Wei, Zehong; Luo, Wenjie (Frontiers in Marine Science, 2025)
IntroductionFishmeal is beneficial to the growth performance of grass carp. However, it remains unclear whether fishmeal can enhance the flavor of muscle, and contribute to the regulatory mechanisms involved in its interaction with the intestinal microbiome. MethodsIn this study, grass carp (70.01 ± 5.34 g) were fed with diets containing 0% (FL), 3% (FM), and 6% (FH) fishmeal for 60 days. The growth performance, intestinal and muscle histomorphology, intestinal microflora, and muscle volatile compounds (VOCs) were evaluated.ResultsThe results showed that compared with the FL group, the final body weight (FBW), weight gain rate (WGR), specific growth rate (SGR), and intestinal villus height of grass carp in the FM and FH groups were significantly increased. Compared with the FL and FM groups, the muscle fiber density in the FH group was significantly increased, and the muscle fiber diameter was significantly reduced. Microbial data analysis found that the three treatment groups were well separated in the NMDS plot, and different levels of fishmeal had a significant impact on microbial community composition (Stress = 0.084). In the LefSe analysis (LDA value > 3.0), Actinobacteria in the FL group, Petrimonas in the FM group, Bacteroides paurosaccharolyticus, and Erysipelatostridiaceae in the FH group all showed significant responses. The intestinal microbiota composition was closer in the FM and FH groups compared with the FL group. GC-IMS analysis indicated that 53 VOCs were detected in the muscle. The FL group had fewer VOCs, and most of the VOCs had lower contents than those in the FH group. Spearman correlation analysis showed that aldehydes were significantly positively correlated with Corynebacterium, Bacteroides, Cetobacterium, Erysipelatoclostridium, Aeromonas, Shewanella, and Vibrio. DiscussionBased on the evaluation of growth performance, intestinal morphology, and microflora, the diet containing 3% fishmeal is suitable. However, the muscle fiber characteristics and VOCs profile of grass carp fed with 6% fishmeal diet is superior to that of the 3% fishmeal group.